Analisis Hukum Praktik Pemagangan Di Indonesia Dalam Perspektif Pasal 27 Ayat (2) UUD 1945 Terhadap Pemenuhan Hak - Pirmansyah, Yudi Syarif; Jatnika, Hendra; Ruslih, Tatang; Suswandi, Suswandi; Istiqomah, Shinta (DPPM Universitas Pelita Bangsa, 2025)
This study aims to examine PERMENAKER No. 6 of 2020 concerning the Implementation of Domestic Internships, reviewed from Article 27 paragraph (2) of the 1945 Constitution which guarantees the right of every citizen to obtain decent work and a decent living. This study uses a normative legal method by analyzing laws and regulations, legal theory, and expert opinions. The results of the study found that the regulations governing current internships do not fully provide certainty and legal protection for interns, especially regarding the right to decent wages and social security